PENGARUH GROWTH OPPORTUNITY DAN DEBT COVENANT TERHADAP KONSERVATISME AKUNTANSI - Hapsari, RR. Prima Dita; Aprilia, Weri (Media Ekonomi, 2025)
Accounting conservatism assumes that companies are faced with future economic uncertainties, so that the measurement and recognition of these figures is done carefully and accountably. This study aims to examine the effect of growth opportunity and debt covenant on conservatism accounting. The independent variables in this study are growth opportunity proxies to market to book value of equity (MBVE) and debt covenant proxies to debt to equity ratio (DER). In this study, the method used for sampling is purposive sampling method obtained as many 27 manufacturing companies in the consumer goods industry sector listed in BEI during 2017-2021. Therefore, the amount of data observed in this study amounted to 135 data. Then, the existing data were analyzed using Statistical Package for Social Sciences (SPSS) 24 software with multiple linear regression analysis method. The results showed that growth opportunity had a significant effect on the conservatism accounting, while debt covenant in this study did not effect on conservatism accounting. On the other hand simultaneously indicates a positive influence between the independent and dependent variables.